Measuring intangible assets - the state of the art - Marr, Bernard (Measuring business excellence ;, 2004)
Intangible assets have become important factors of value creation in today's knowledge economy. However, individually they are often commodities and only create value in combination with other production factors. Therefore, in order to manage for performance and value, companies and their managers, as well as their investors, need a better understanding of their role as part of the entire value creation system of an organization. The article outlines possible features of an improved management and corporate reporting model. In order to objectively measure the productivity and efficiency of the.